Risk Assessment of Salmonella spp. Exposure Among Chicken Farm Workers in Phatthalung Province, Southern Thailand - Onmek, Nutthajit; Mueangdee, Nongyao (Kesmas, 2025)
This study examined the risk of Salmonella spp. exposure among chicken farm workers by evaluating occupational health management practices. The probability of exposure was determined by assessing the number of contamination points. Sampling for Salmonella spp. contamination was conducted at 7 and 45 days of chicken batches across five areas, alongside evaluation of worker behaviors to assess exposure risk. Three of the 12 large closed-system farms, each housing >10,000 chickens, were selected. Results indicated that boots were the most contaminated items. Workers generally adhered to habitual boot-wearing, which reduced the risk of exposure. Moderate levels of workers' exposure prevention practices, combined with good farm environmental management, resulted in low contamination levels. Reducing Salmonella spp. accumulation was therefore crucial for minimizing contamination. In brief, the chicken farm workers in Phatthalung face measurable risks of Salmonella spp. Exposure reduction, strengthening occupational health management, and improving workplace practices are essential to mitigating these risks and protecting both farm workers and the broader community.